The language of the integrative theory: reflections on Gerd Jüttemann's Historische psychologie: - Cornejo, Carlos (Culture & psychology, 2014)
Gerd Jüttemann has recently published a programmatic article in the German journal Erwägen-Wissen-Ethik(Deliberation-Knowledge-Ethics) in which he explains the maintenets of his theoretical approach Historical psychology. We analyze the characteristicsof the metalanguage used by the author to produce the integration, questioning its effectiveness given its level of abstraction. Although integrative theories are necessary,a pluralism of grammars seems more promising than approaches favoring one unitary language.